Perturbation and Stability of Continuous Operator Frames in Hilbert C∗-Modules - Abdeslam Touri; Hatim Labrigui; Mohamed Rossafi; Samir Kabbaj (Journal of Mathematics)
Frame theory has a great revolution in recent years. This theory has been extended from the Hilbert spaces to Hilbert C∗-modules. In this paper, we consider the stability of continuous operator frame and continuous K-operator frames in Hilbert C∗-modules under perturbation, and we establish some properties.